THE ROLE MODEL OF HEALTH TRUST IN IMPROVING BPJS SERVICE UTILIZATION: META-ANALYSIS - Irma Finurina Mustikawati; Endang Sutisna Sulaeman; Achmad Arman Subijanto; Suminah Suminah (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
Health is an investment for the community, because health is the basic capital needed by all people to be able to work according to their respective duties and responsibilities, so as to produce something that is beneficial to themselves and their families. This research uses meta-analysis method. Global and domestic literature searches leveraging the EBSCO, ScienceDirect, and Proquest databases. Based on the findings from this study, it can be concluded that HBM can help identify significant determinants of health behavior and address issues related to privacy and confidentiality, which are important factors in influencing people's intention to use online services. However, the process of adopting e-services in Indonesia may be hampered by low government trust, which requires further attention and efforts from policy makers